2024
DOI: 10.1186/s12912-024-01833-z
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of cybersickness in virtual nursing simulation: a German longitudinal study

Maria Biniok,
Theresa A. Forbrig,
Paul Gellert
et al.

Abstract: Background Innovative educational approaches such as simulation-based nursing education using virtual reality (VR) technologies provide new opportunities for nursing education. However, there is a lack of information on side effects, especially health-related side effects, of head-mounted displays (HMDs) on the human body when using VR devices for nursing simulation. This study aims to validate the German version of the Virtual Reality Sickness Questionnaire (VRSQ) and to evaluate its associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], the authors reported one typing error in Table 2 , line Disorientation is written: ([2]/12)*100 but it should be: ([2]/15)*100.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported one typing error in Table 2 , line Disorientation is written: ([2]/12)*100 but it should be: ([2]/15)*100.…”
mentioning
confidence: 99%